Comprehensive Molecular Profiling for Relapsed/Refractory Pediatric Burkitt Lymphomas-Retrospective Analysis of Three Real-Life Clinical Cases-Addressing Issues on Randomization and Customization at the Bedside - Polaskova, Kristyna; Merta, Tomas; Martincekova, Alexandra; Zapletalova, Danica; Kyr, Michal; Mazanek, Pavel; Krenova, Zdenka; Mudry, Peter; Jezova, Marta; Tuma, Jiri; Skotakova, Jarmila; Cervinkova, Ivana; et al. (Frontiers in oncology, 2019)
UNLABELLED: In order to identify reasons for treatment failures when using targeted therapies, we have analyzed the comprehensive molecular profiles of three relapsed, poor-prognosis Burkitt lymphoma cases. All three cases had resembling clinical presentation and histology and all three patients relapsed, but their outcomes differed significantly. The samples of their tumor tissue were analyzed using whole-exome sequencing, gene expression profiling, phosphoproteomic assays, and single-cell phosphoflow cytometry. These results explain different treatment responses of the three histologically identical but molecularly different tumors. Our findings support a personalized approach for patient with high risk, refractory, and rare diseases and may contribute to personalized and customized treatment efforts for patients with limited treatment options like relapsed/refractory Burkitt lymphoma. SUMMARY: The main aim of this study is to analyze three relapsed Burkitt lymphoma patients using a comprehensive molecular profiling, in order to explain their different outcomes and to propose a biomarker-based targeted treatment. In cases 1 and 3, the tumor tissue and the host were analyzed prospectively and appropriate target for the treatment was successfully implemented; however, in case 2, analyses become available only retrospectively and his empirically based rescue treatment did not hit the right target of his disease.
Keywords: Burkitt lymphoma; theranostics; targeted therapy; precision medicine; pediatric oncology